Vertical transmission of Trypanosoma cruzi infection: Quantification of parasite burden in mothers and their children by parasite DNA amplification - Bua, Jacqueline Elena (2012)
The relationship between parasite burden and vertical transmission of Trypanosoma cruzi was studied in pairs of chronically infected women and their children in a non-endemic area. Parasitemia was quantified by quantitative polymerase chain reaction (qPCR) in the peripheral blood amplifying a nuclear T. cruzi DNA and expressed as equivalent amounts of CL Brener parasites DNA per ml (eP/ml). Similar levels of parasitemia were found in non-transmitting pregnant women and in non-pregnant women: 1.8±0.5 and 1.5±0.7 eP/ml, respectively. In women pregnant with infected children parasitemia was 11.0±2.7 eP/ml (n=20). In 12 of their neonates the infection was detected by microscopic observation of the parasites in peripheral blood in the 1st month of age. These children had variable levels of parasitemia (13 000±7000 eP/ml), that were about 600-fold higher than that found in their mothers. To our knowledge, this is the first quantitative evaluation of parasitemia in these three groups of women and in their congenitally infected children. These parasite quantifications could be a basis to plan the control of mother-to-child transmission of T. cruzi.